A Predictive Study Between Anxiety and Fear of COVID-19 With Psychological Behavior Response: The Mediation Role of Perceived Stress - Sharif Nia, Hamid; She, Long; Kaur, Harpaljit; Boyle, Christopher; Khoshnavay Fomani, Fatemeh; Hoseinzadeh, Esmaeil; Kohestani, Daniyal; Rahmatpour, Pardis (Frontiers in Psychiatry, 2022)
Objective: Despite the abundance of studies linking fear and anxiety to Covid-19, there are limited studies that examine how these elements impact psychological behavioral responses, especially in Iran. The aim of this study was to investigate the relationship between anxiety and fear of COVID-19 with psychological behavior response, whether this relationship is mediated by role of perceived stress among Iranian population during the COVID-19 pandemic. Methods: A predictive cross-sectional study was used to investigate the relationships between COVID-19 anxiety syndrome, fear of the COVID-19 with psychological behavioral responses due to the pandemic and the mediating role of the COVID-19 perceived stress in these relationships. Results: The current study revealed that during the COVID-19 pandemic, fear and anxiety of COVID-19 can influence the psychological behavioral responses of the individuals, however this can be explained through perceived stress. Conclusion: As such, the current study points to the individuals who perceived high stress due to COVID-19 were more likely to comply with guidelines, which was contrary to the findings of previous studies. The current study findings are applicable for health policy-makers in order to help them in understanding human behavior for developing health promotion programs and also for fostering resilience among the general population.